2017
DOI: 10.1044/2017_jslhr-h-16-0474
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Working Memory in Children With Cochlear Implants

Abstract: Purpose Verbal working memory in children with cochlear implants and children with normal hearing was examined. Participants Ninety-three fourth graders (47 with normal hearing, 46 with cochlear implants) participated, all of whom were in a longitudinal study and had working memory assessed 2 years earlier. Method A dual-component model of working memory was adopted, and a serial recall task measured storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 66 publications
5
40
0
Order By: Relevance
“…The latter findings suggested that encoding may contribute to pediatric CI users' individual differences in short-term and working memory, supplementing an earlier discovery that processing operations during storage were related to span (Pisoni & Cleary, 2003). Additional findings implicating CI users' vocabulary knowledge as the primary predictor for word span also suggested a role for retrieval mechanisms (Nittrouer et al, 2017). These previous results led us to test whether individual variation in memory span performance was better accounted for by measures related to processing operations during encoding and retrieval-such as recoding speed and vocabulary knowledge-or measures related to storage, such as nonword repetition.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The latter findings suggested that encoding may contribute to pediatric CI users' individual differences in short-term and working memory, supplementing an earlier discovery that processing operations during storage were related to span (Pisoni & Cleary, 2003). Additional findings implicating CI users' vocabulary knowledge as the primary predictor for word span also suggested a role for retrieval mechanisms (Nittrouer et al, 2017). These previous results led us to test whether individual variation in memory span performance was better accounted for by measures related to processing operations during encoding and retrieval-such as recoding speed and vocabulary knowledge-or measures related to storage, such as nonword repetition.…”
Section: Discussionsupporting
confidence: 53%
“…Computational models of short-term memory demonstrate that larger vocabularies support redintegration processes by providing fast access to many possible lexical templates (Gupta & Tisdale, 2009). Indeed, pediatric CI users' vocabulary knowledge has been found to predict their performance on a word span task (Nittrouer et al, 2017). Redintegration processes also depend on stimulus characteristics.…”
Section: Three Stages Of Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, we agree that it is likely that children with CIs may have an especially difficult time encoding and representing stimuli that lend themselves well to verbal rehearsal (Cleary et al, 2001;Gremp, 2011;Nittrouer, Caldwell-Tarr, Low, & Lowenstein, 2017), and so perhaps this is where the greatest group differences on SL tasks are likely to be found. On the other hand, there is some evidence that children with CIs show difficulty even with nonverbal sequencing tasks (e.g., .…”
Section: Recent Studies Of Sl In Individuals With Hearing Impairmentmentioning
confidence: 64%
“…Therefore, they may be expected 1.3. Children with Cochlear Implants to perform more poorly compared to peers with TH, a finding observed in a number of studies (Akçakaya et al, 2019;Edwards et al, 2011;Nittrouer et al, 2017;Pixner et al, 2014). Language ability of importance for non-verbal cognitive measures that benefit from verbal strategies.…”
Section: Cognitive Abilitymentioning
confidence: 89%